Developing K-Workers' Competencies Framework for Undergraduate University Students - Santoso, Teguh Iman; Hassan, Razali (Journal of Technical Education and Training, 2018)
The right competencies are required by students in the field of work in industry. A review of the literature study shows that there are several models that can be used as principles in shaping student competencies. The objective of this study is to build competency models for students that are in accordance with the field of work in the industry. Problems being discussed in this study are (1) How is the gap between competency of students and industrial needs? (2) What are the main dimensions of student competence? (3) What are the elements of competence in the 'k-worker' dimension? (4) How to design a 'k-worker' framework? This research applied qualitative method based on the support of quantitative data. The framework design of this study are exploratory by using the Modified Delphi technique from experts in the field of electrical / electronic to obtain qualitative data, which then a questionnaire to obtain quantitative data was distributed to students in four universities in Batam. Analyzed through demographic analysis, descriptive analysis, qualitative data analysis through interview and document review then analyzed by SEM. SEM analyze shows a K-Workers Model that fit to the experts and perceptions among students. The study shows that there are a huge gap between students and the industrial needs, student competencies are not as expected by the industry as users of labor services that caused by several factors. In addition, the study plan shows that the dimensions and elements of competence are needed by students. From the quantitative study, the distribution of questionnaire to all respondents in the form of technical faculty students from four universities in Batam and processed with Structural Equation Modeling (SEM) obtained a model of competence "k-workers". This research should be done because of it significance in terms of theory, practice, and policy formation. The findings of this research are important in contributing to certain parties, particularly the Education and Training Institutions, industry and Employment Empowerment and testing and certification organizer.